Funeral practices and grief. Issue 3 (1st September 2020) - Birrell, John; Woodthorpe, Kate; Stroebe, Margaret; Rumble, Hannah; Schut, Henk; Corden, Anne; Anadria, Daniel; Smith, Yvette; Newsom, Cate
Abstract: Does restricting the ceremonial/ritual arrangements around a cremation to a minimum have a negative association with grief over time? This question has increasingly concerned professionals in the funeral industry as well as those in healthcare capacities working with bereaved persons. We examined the relationship between cremation arrangements and levels of grief. Bereaved people in the UK completed questionnaires 2 to 5 months post-loss and a year later (N=233 with complete data). Complexity of the cremation service was not significantly related to grief; neither was satisfaction with arrangements (which was typically high). Results suggested that it makes no difference to grief whether a more minimalistic or elaborate funeral ceremony is chosen under conditions where the bereaved feel free to make choices that best suit their situation. We concluded that the funeral industry seems to be offering bereaved people an appropriate range of cremation arrangement choices to meet their needs. Important limits to generalizability are discussed. That funeral services serve multiple functions for bereaved persons is emphasized.